2022-RA-1154-ESGO Ovarian cancer management. Who cares for the Patient? A single case observational study. (20th October 2022) - Krankenberg, David Johannes; Pietzner, Klaus; Muallem, Mustafa Zelal; Lee, Marlene; Sehouli, Jalid
Abstract : Introduction/Background: Ovarian cancer is primarily diagnosed in advanced stages, and thus far, no sensitive screening is available. Therefore, in newly diagnosed patients, treatment and evaluation have become highly specialized, and an individually adapted approach should be made in each case by interdisciplinary cooperation. The present study aims to display the variety and extent of medical specialities and personnel resources involved in today's therapy algorithm to efficiently treat patients with advanced ovarian cancer following a patient's journey. Methodology: A patient diagnosed with ovarian carcinosarcoma FIGO IIIb was selected for a single case observational study. The period under observation (total=22d) compromised preliminary evaluation, outpatient imaging, the in-patient stay for cytoreductive surgery and ended with the postoperative case discussion at our interdisciplinary tumor conference. Data were obtained by self-reporting and by patient file review. As part of standard care, multidisciplinary evaluation and treatment were performed. Results: Patient-tracking demonstrated an interdisciplinary cooperation of 12 medical specialities (n=62 physicians; men n=39, 62, 7%; women n=23, 37, 3%), 8 different types of nursing staff (n=59; men n=13, 22%; women n=46, 78%) and 9 different types of peri-operative/administrativ staff (n=23; men n=4, 17, 4%; women n=19, 82, 6%) with a total number of n=144 individuals. Interaction with the patient was furthermore divided into direct contacts (n=199; 76%) and indirect contacts (n=63; 24%), without face-to-face interaction, with a total number of n=262 patient-oriented contacts. Conclusion: Modern treatment of advanced ovarian cancer requires multidisciplinary medical therapy, a holistic patient-centered approach and close dialogue as a team in specialized hospitals. The present study demonstrates the diversity of physicians, medical staff and interdisciplinary teamwork that is implemented in the evaluation and treatment of a single patient and underlines the need for a structured multiprofessional communication algorithm.